22q11 deletion syndrome: a review of the neuropsychiatric features and their neurobiological basis - Squarcione C (Dove Medical Press, 2013)
Chiara Squarcione, Maria Chiara Torti, Fabio Di Fabio, Massimo Biondi Department of Neurology and Psychiatry, Sapienza University of Rome, Rome, Italy Abstract: The 22q11.2 deletion syndrome (22q11DS) is caused by an autosomal dominant microdeletion of chromosome 22 at the long arm (q) 11.2 band. The 22q11DS is among the most clinically variable syndromes, with more than 180 features related with the deletion, and is associated with an increased risk of psychiatric disorders, accounting for up to 1%–2% of schizophrenia cases. In recent years, several genes located on chromosome 22q11 have been linked to schizophrenia, including those encoding catechol-O-methyltransferase and proline dehydrogenase, and the interaction between these and other candidate genes in the deleted region is an important area of research. It has been suggested that haploinsufficiency of some genes within the 22q11.2 region may contribute to the characteristic psychiatric phenotype and cognitive functioning of schizophrenia. Moreover, an extensive literature on neuroimaging shows reductions of the volumes of both gray and white matter, and these findings suggest that this reduction may be predictive of increased risk of prodromal psychotic symptoms in 22q11DS patients. Experimental and standardized cognitive assessments alongside neuroimaging may be important to identify one or more endophenotypes of schizophrenia, as well as a predictive prodrome that can be preventively treated during childhood and adolescence. In this review, we summarize recent data about the 22q11DS, in particular those addressing the neuropsychiatric and cognitive phenotypes associated with the deletion, underlining the recent advances in the studies about the genetic architecture of the syndrome. Keywords: 22q11 deletion syndrome, microdeletion, neuropsychiatric disorders, cognitive impairments